The Government Procurement Contract (A Juridical Review between Civil Code VS Presidential Regulation) - Situmeang, Tomson (JURNAL AKTA, 2025)
There are two types of provisions that govern agreements, namely private law and public law. PBJP is a government activity that is realized through a contract, but the contract is unique because it is hybrid, it is a private contract but is subject to the provisions of public law. This research aims to conduct a critical review of the differences or inconsistencies between the rules regarding Government Procurement of Goods/Services (PBJP) contained in Presidential Regulation Number 46 of 2025 and the fundamental principles of agreement law contained in the Civil Code (KUHPerdata). The theoretical foundation of this research rests on the theory of legal certainty and Hans Kelsen's and Nawiasky's theory of tiered legal norms (Stufenbau Theorie). Methodologically, it adopts a normative juridical approach, specifically through statutory and conceptual analyses. The results showed that the regulation of PBJP through the Perpres normatively contradicts the principle of hierarchy of legal norms because the Civil Code as lex generalis is a product of law that is higher than the Perpres. Ironically, the Perpres plays a dominant role in the practice of implementation and dispute resolution of the PBJP contract, including when there is a wrong interpretation that makes default a corruption crime. The main finding of this article is the importance of adjusting the regulation of PBJP with the principles of civil law and hierarchy of norms, as well as the need for the establishment of a separate law that comprehensively regulates PBJP. Thus, the legal regulation of PBJP must be placed in the national legal system consistently in order to create legal certainty and prevent overlapping between public and private norms.